Fundamentals of fluid mechanics - Faris, Waleed Fekry; Mohyuddin, Muhammad Raheel; Ismail, Ahmad Faris (IIUM Press, 2009)
This book deals with the fundamentals of fluid mechanics that are taught at the undergraduate level. It can also be used as a refresher course for engineers who need to review the subject but do not have the time to go through lengthy books. The book features aspects which are not available in current textbooks, such as, it is simple, clear, brief and goes straight to the point, without containing much discussion, making it easier for the reader to understand. The book also stresses on the clarity of derivations and assumptions underlining the fluid mechanics principles and is recommended to students, engineers, and academicians.